Gelling Properties of Chia Seed and Flour - Coorey, Ranil; Tjoe, A.; Jayasena, Vijay (Wiley-Blackwell Publishing, Inc., 2014)
Healthy oil profile of chia has been well established. Chia could also be a good source of gel. The characteristics of chia gel were studied and compared to guar gum and gelatin which are commonly used in the food industry. The properties tested were water and oil holding capacities, viscosity, line-spread; emulsification activity and freeze–thaw stability. The extracted chia gels from seeds and flour were analyzed for moisture, ash, protein, crude fiber, oil, and fatty acid profile. Water-holding capacity, oil-holding capacity, viscosity, emulsion activity, and freeze–thaw stability of the extracted chia seed gel were similar to guar gum, and gelatin. Chia gel is a polysaccharide based gel mainly consists of crude fiber (58%) and carbohydrate (34%). Extracted chia seed gel has a great potential in food formulations as thickening agent, emulsifying agent, and as a stabilizer.